Pengaruh Disiplin Kerja Dan Lingkungan Kerja Terhadap Kinerja Karyawan: Survei Pada Karyawan Produksi Lemona Cake & Bakery Tasikmalaya - Dhea Aprilyani; Barin Barlian; Suci Putri Lestari (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2023)
This study aims to determine and analyze the effect of work discipline and work environment on employee performance in the production of Lemona Cake & Bakery Tasikmalaya. The population in this study were production employees at Lemona Cake & Bakery with a survey approach and technical data analysis using multiple linear regression. Based on the data that has fulfilled the validity test, reliability test, and classic assumption test, it is processed to produce a regression equation as follows. The test results show that simultaneously work discipline and work environment have a significant effect on employee performance, while the work environment has no partial effect on employee performance Lemona Cake & Bakery Tasikmalaya.